2015
DOI: 10.2147/copd.s87714
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between anthropometric indicators and walking distance in patients with chronic obstructive pulmonary disease

Abstract: BackgroundExercise intolerance is a major issue affecting many people with COPD. Six-minute walking distance (6MWD) is a widely used indicator of exercise capacity in patients with COPD. The process is strenuous and time-consuming, especially for patients who have muscle wasting. Anthropometric indicators that reflect body lean mass, such as body mass index (BMI), mid-arm circumference (MAC), and calf circumference (CC), may have value in predicting exercise intolerance.PurposeThis study attempted to determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…The paper by Hsu et al showed that the CC could be applied to predict emerging care needs in older adults [ 31 ]. Moreover, the CC was significantly associated with exercise intolerance and the functional capacity in patients with chronic lung disease [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…The paper by Hsu et al showed that the CC could be applied to predict emerging care needs in older adults [ 31 ]. Moreover, the CC was significantly associated with exercise intolerance and the functional capacity in patients with chronic lung disease [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Prior research has primarily used values based on anthropometric indicators [26] and gait speed. [8,11] In relation to the 4MGS test, our cut-off value of 4 seconds (or 1 m/s) is consistent with previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings that ordinal scores of 2 or less collected using the 5STS test, and a time over 13 seconds or more, can usefully discriminate poor 6MWT performance, are novel in this field. Prior research has primarily used values based on anthropometric indicators [ 26 ] and gait speed. [ 8 , 11 ] In relation to the 4MGS test, our cut-off value of 4 seconds (or 1 m/s) is consistent with previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 The causes and mechanisms of exercise intolerance in these patients are still complex and involve respiratory function, gas exchange limitations and reduced peripheral skeletal muscle mass. 9,10 Thus, it is extremely important to identify and understand what changes in pulmonary volumes and reduction of respiratory muscle strength may impact the submaximal and maximal exercise capacity in patients with moderate -very severe COPD. Our aim was to evaluate the influence and association of respiratory variables (pulmonary function and respiratory muscle strength) on maximal and submaximal exercise capacity of patients with COPD.…”
Section: Introductionmentioning
confidence: 99%